Tourist Potential of Ukraine: Challenges and Prospects of the Post-War Time - LEVYTSKA, Inna; KLYMCHUK, Alona; SHESTAKOVA, Anna; BILETSKA, Natalia (Journal of Environmental Management and Tourism, 2023)
The tourism industry is one of the sectors of the global economy most affected by the pandemic. At the same time, in 2022, having not yet fully recovered from the impact of quarantine restrictions, it was forced to face a completely new challenge for itself - large-scale military operations on a large part of the European territories. It was Ukraine and its tourism sector that suffered the most from the war, and since the prospects for the end of the war are very uncertain, the issue of preserving the country’s tourism potential, finding ways to speed up its recovery and post-war development of the tourism sector of Ukraine are gaining particular relevance. To substantiate the prospects and challenges for the tourism potential of Ukraine in the post-war period and to determine the key directions of actions of the state and business for its preservation, effective use and expansion during the war period. The methodological basis of the study was made up of general scientific and special methods of economic theory, in particular, methods of theoretical generalization and comparative analysis and synthesis for the purpose of researching all processes and phenomena of the tourism sector of Ukraine in interdependence and interconnection. In the course of the study, statistical materials of the European Union and Ukraine were applied on the functioning of the tourism sector of the economy and processed using the methods of statistical analysis: comparison, grouping, calculation of average values and proportions, as well as analytical data and assessments of specialized state agencies of Ukraine were used. A comparison of the impact of the COVID-19 pandemic on the development of the tourism sector of Ukraine and individual EU countries and the shares of tourism trade turnover in their GDP is made, which has revealed to note the low level of use of Ukraine’s own tourism potential in the pre-war period. The key strengths and weaknesses of the tourism sector of Ukraine according to the version of the World Economic Forum have been studied and the prospects and consequences for them as a result of the war have been substantiated. A number of strategic courses of action for the state and business are proposed, based on the main possible prospects for the duration of active hostilities.